Assessment of Climate Change Impacts on the Distribution of Endangered and Endemic Changnienia amoena (Orchidaceae) Using Ensemble Modeling and Gap Analysis in China - Ting Liu; Hanwei Cai; Guangfu Zhang (Ecology and Evolution)
ABSTRACT Climate change has significant impacts on the distribution of orchids. The endemic and endangered orchids are more susceptible to climate change than widely distributed orchids. To date, little is known concerning the response of endangered Changnienia amoena, endemic to China, to different climate scenarios. Here, we build an ensemble model comprising random forest model, maximum entropy model, and gradient boosting model in Biomod2 package to project its potential distribution in China, evaluate its current protective effectiveness, and identify its conservation gaps in China by determining the C. amoena population range within the natural protected areas. The outcomes showed that the four key environmental factors influencing its distribution were mean diurnal temperature range, minimum temperature of the coldest month, temperature seasonality, and precipitation of the warmest quarter. This orchid was currently distributed mainly in southern Anhui, central and western Hubei, western Hunan, southern Shaanxi, and eastern Sichuan province. The total suitable area of C. amoena was 58.33 × 104 km2, only accounting for 6.08% of China's total territory, which is larger than known. However, only 4.48% of the suitable area is located within national nature reserves and 3.33% within provincial nature reserves, respectively. During the last inter glacial and mid‐holocene, its suitable areas were larger than the current. Under six future climate scenarios, its suitable areas may decrease averagely by 2.26% relative to the current, with severe habitat fragmentation. Collectively, the centroid of C. amoena is expected to shift towards the southeast in the future. Therefore, our findings demonstrate that climate change has an adverse effect on its potential distribution. We recommend expanding protected areas or establishing new conservation sites for C. amoena in China. Furthermore, our study can help to inform the development of conservation management strategies for other endangered Chinese endemic orchids under climate change.